UJI BANDING METODE ANALISIS KONVENSIONAL DAN INSTRUMENTAL UNTUK PENENTUAN KALSIUM DAN FOSFOR - Hendro Santoso M (Research Center for Chemistry - LIPI, 1997)
Analysis of calcium and phosphor has been done by using conventional and instrumental methods. Lorenz gravimetric method was employed to determine phosphor, whereas permanganometric methods used to determine calcium. Spectronic molibdovanadophosphate and atomic absorption spectrophotometric methods were used as control for phosphor and calcium respectively. Samples analysed in this study were molasses and driedfaeces.Results show that there is no significant effect on analysis phosphor by using both Lorenz gravimetric method and its control. Similarly, permanganometrlc methods result in the same value with its control.